Agronomic and economic feasibility indicators for cowpea-vegetable under green manure in a semiarid environment - Silva, Josimar; Bezerra Neto, Francisco; Lima, Jailma; Barros Júnior, Aurélio; Nunes, Renato Leandro; Chaves, Aridênia (Revista Ciência Agronômica, 2020)
Two experiments were conducted in different areas of the Rafael Fernandes Experimental Farm, located in Lagoinha district, 20 km from Mossoró municipality (RN), in the period from June to September of the years of 2015 and 2016 with the objective of evaluating and estimating agronomic and economic feasibility indicators of cowpea-vegetable as a function of amounts of hairy woodrose (Merremia aegyptia (L.) Urb.) biomass incorporated into the soil in two crops. Treatments consisted of the following amounts of hairy woodrose biomass: 20, 35, 50 and 65 t ha-1 on a dry basis. The cultivar of cowpea-vegetable planted was “BRS Itaim”. The evaluated characteristics were: length of green pods, number of green pods per m2, productivity and dry mass of green pods, weight of 100 green grains, yield and dry mass of green grains. In addition, the following economic indicators were evaluated: gross income, net income, rate of return and profitability index. The optimization of the agronomic efficiency of the cowpea-vegetable was obtained in the amount of 45 t ha-1 of hairy woodrose biomass incorporated into the soil and the optimization of the agroeconomic viability of the cowpea-vegetable cultivation was reached in the quantity of hairy woodrose biomass of 37.70 t ha-1 added to the ground. The first growing crop yielded better agroeconomic efficiency of cowpea-vegetable than the second crop. The use of hairy woodrose as green manure is economically feasible and recommended to the farmer in the production of cowpea-vegetable under the evaluated conditions.